2018
DOI: 10.1111/2047-3095.12205
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Respiratory Nursing Diagnoses and Accuracy of Clinical Indicators in Preterm Infants

Abstract: Early recognition of respiratory conditions can support safe interventions to ensure appropriate outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 24 publications
(54 reference statements)
1
7
0
7
Order By: Relevance
“…When we analyzed the diagnosis ISV, the DC “increase in metabolic rate,” identified by altered vital signs, such as blood pressure, body temperature, HR, and respiratory rates (Guyton & Hall, ), presented the highest sensitivity and NPV values, but not good efficiency values, based on the very low specificity and VPP values. This finding was in agreement with a previous study, in which the presence of this DC did not confirm the presence of ISV (Avena et al., ). “Increase in metabolic rate” was not considered accurate to define ISV in the present study, since alterations of the vital signs were present in the entire sample explaining the high value of sensitivity for this ND.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…When we analyzed the diagnosis ISV, the DC “increase in metabolic rate,” identified by altered vital signs, such as blood pressure, body temperature, HR, and respiratory rates (Guyton & Hall, ), presented the highest sensitivity and NPV values, but not good efficiency values, based on the very low specificity and VPP values. This finding was in agreement with a previous study, in which the presence of this DC did not confirm the presence of ISV (Avena et al., ). “Increase in metabolic rate” was not considered accurate to define ISV in the present study, since alterations of the vital signs were present in the entire sample explaining the high value of sensitivity for this ND.…”
Section: Discussionsupporting
confidence: 94%
“…In adult postoperative cardiac surgery patients, the DC "abnormal breathing pattern" and "pursed-lip breathing" showed high sensitivity; whereas, "altered chest excursion" and "prolonged expiration phase" were considered specific for this diagnosis (Sousa et al, 2016). In a study exploring the IBP diagnosis in a pediatric population, the DCs "use of accessory muscles to breathe" and "abnormal breathing pattern" were accurate (Avena et al, 2019). In our study, regression analysis has shown only the cluster "use of accessory muscles to breathe ± tachypnea" to be a predictor for IBP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…International collaboration has been recognized as a tool that enhances the ability to address complex problems from a variety of perspectives (Gallani, 2016). A priority in terms of diagnostic development is clinical research, preferably conducted by researchers from different countries (Avena et al, 2019;Dias Emidio et al, 2020;Linch et al, 2014). This will allow nurses to test their ability to propose diagnostic hypotheses in different clinical settings, based on more consistent designs and analyses.…”
Section: Priorities and Possibilities For International Collaborationmentioning
confidence: 99%
“…Anxiety is caused by the removal of a child from his or her family and by being with strangers and performing invasive and painful procedures (Gomes & da Nóbrega, 2015). Previous studies have also identified ineffective breathing (Avena et al, 2019;Gomes & da Nóbrega, 2015) and impaired gas exchange (Avena et al, 2019) as problem-oriented nursing diagnoses, but they were not observed in randomly selected nursing records.…”
Section: Discussionmentioning
confidence: 99%